Ca2+ mediates transcription factor PuDof2.5 and suppresses stone cell production in pear fruits - Zhang, He; Gao, Siyang; Wang, Tianye; Xu, Mingyang; Li, Xinyue; Du, Guodong (Frontiers in Plant Science, 2022)
Stone cells are sclerenchyma cells formed by the deposition of lignin, what is the most significant factor limiting the quality of pears. Ca2+ was known to inhibite stone cells in pear fruit, but the underlying molecular mechanisms remains unclear. Here, our study revealed exogenous CaCl2 (Ca2+) treated ‘Nanguo’ pear (Pyrus ussuriensis) suppressed the synthesis of lignin and stone cell production. We further compared the transcriptomes of the CaCl2-treated and control fruits using RNA-seq, identified a transcription factor, PuDof2.5, and its targets gene PuPRX42-like (lignin polymerase gene) expression decreased in CaCl2-treated samples, which are involved in suppressing lignin biosynthesis in pear fruit. And PuDof2.5 was found to bind directly to the PuPRX42-like promoter and induced its transcription. Taken together, Our results revealed that Ca2+ modulated the key lignin biosynthetic transcription factor PuDof2.5 to suppresses stone cell production in pear fruits.